2013
DOI: 10.1016/j.orggeochem.2013.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive glycerol ether lipid fingerprints through a novel reversed phase liquid chromatography–mass spectrometry protocol

Abstract: Glycerol ether lipids have been developed as proxies to reconstruct past environmental changes or in their intact polar form to fingerprint the viable microbial community composition. However, due to the structural complexity, the full characterization of glycerol ether lipids requires separate protocols for the analysis of the polar head groups and the alkyl chain moieties in core ether lipids. As a consequence, the valuable relationship between core ether lipid composition and specific polar head groups is o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
99
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

7
3

Authors

Journals

citations
Cited by 85 publications
(103 citation statements)
references
References 45 publications
3
99
1
Order By: Relevance
“…in 5 min, followed by a gradient to 65 % B in 55 min. The column was then flushed with 90 % B for 10 min and re-equilibrated with 100 % A for 10 min (Zhu et al, 2013). Lipid identification was based on retention time as well as accurate molecular mass and isotope pattern match with known sum formulas in full scan mode and MS2 fragment spectra.…”
Section: The Sources Of Isolation Of Strains S5mentioning
confidence: 99%
“…in 5 min, followed by a gradient to 65 % B in 55 min. The column was then flushed with 90 % B for 10 min and re-equilibrated with 100 % A for 10 min (Zhu et al, 2013). Lipid identification was based on retention time as well as accurate molecular mass and isotope pattern match with known sum formulas in full scan mode and MS2 fragment spectra.…”
Section: The Sources Of Isolation Of Strains S5mentioning
confidence: 99%
“…coupled to an ABSCIEX QTRAP 4500 mass spectrometer (ABSCIEX, Darmstadt, Germany) by a TurboIonSpray ion source set to electrospray ionization (ESI) mode. The samples were chromatographically separated on an ACE3 C 18 column (150 × 2.1 mm; particle size 3 µm) equipped with a guard column using a method modified from Zhu et al (2013). Column temperature was set to 45 °C and eluent A consisted of MeOH/HCO 2 H/14.8 M NH 3 and eluent B was prepared from propan-2-ol/HCO 2 H/14.8 M NH 3 .…”
Section: Analysis Of Intact Polar Membrane Lipidsmentioning
confidence: 99%
“…To this end, Buckles and colleagues (2013) suggested that relative enrichments of an archaeal tetraether lipid, the taxonomically widely distributed glycerol dibiphytanyl glycerol tetraether without cyclopentane rings [i.e. Fortunately, recent advances in the analysis of intact polar lipids (IPLs; Sturt et al, 2004;Wörmer et al, 2013;Zhu et al, 2013) and core lipids (CLs; Knappy et al, 2009;Liu et al, 2012a,b;Becker et al, 2013;Zhu et al, 2014a,b) have already expanded the catalogue of microbial biomarkers and enhanced the ability to find biomarkers associated with the presence of MCG, which could lead to the identification of specific lipid biomarkers. However, the utility of GDGT(0) as universal biomarker for MCG is severely limited due to the widespread occurrence of this lipid in many archaeal phyla (e.g.…”
Section: Introductionmentioning
confidence: 99%